FACTORS OF FORMATION OF UNIVERSITY GRADUATES’ CAREER TRAJECTORIES - L. V. Temnova; O. A. Lizunova (Высшее образование в России)
The article analyzes the trends in the development of university graduates’ career trajectory formation: transition from the model of probable development paths depending on abilities, knowledge, skills (career guidance) – to the model of individual career management, which depends on the individual’s awareness of personal, institutional and social resources and tools, as well as the ability to skillfully apply them, from the paradigm of career planning to the career management paradigm. The authors have analyzed the social practices and identified the groups of factors that shape the graduates’ career trajectories on three levels: 1) personal (key types of literacy and basic skills of the 21st century, the level of awareness (assessment of what is happening, personal motives, resources, skills, knowledge, understanding the context of situation, self-esteem); self-development (the ability to explore, show interest, initiative), the ability to make various choices (evaluation of the importance of choice, awareness of choice), the ability to act purposefully (the ability to implement ideas, skill planning, managing internal and external resources), the ability to inform others on the results of one’s work (reflection, evaluation, etc.), 2) institutional (educational organization, the system of additional education for advanced training, the system of higher education, Federal state educational standards, the National Qualifications Framework, the Register of Professional Standards, various national and international recruitment agencies, employment centers, vocational guidance centers for testing and training, etc.) and 3) the social level (mobility, movement of labor resources, migration, social, resource and natural risks, etc.). The article analyzes the actualization of these factors as applied to the current sociocultural situation in Russia.